Multibeam bathymetry processed data (Kongsberg EM 122 transit dataset) of RV MARIA S. MERIAN during cruise MSM79/2, Atlantic Ocean - Melanie Steffen; Mila Schopenhauer; Stefan Kinne; Harald Sternberg (PANGAEA, 2023)
The multibeam echo sounder (MBES) data was collected from the 07.12.2018 (16:34 UTC) to the 13.12.2018 (10:34 UTC) with the Kongsberg EM122 on RV Maria S. Merian during the transit from Mindelo (Capo Verde) to Bahia de las Minas (Panama) in the Atlantic Ocean (MSM79/2). The deep-water MBES EM122 operates with an acoustic frequency of 12 kHz and a beam opening angle of 2° x 2°. The raw and unprocessed bathymetric and backscatter data is stored in Kongsberg format (*.all), each containing up to 60 min of data. The therein included time, motion and position data (WGS84, geographic) was measured by the Kongsberg Seapath system on board. During the acquisition the echo sounder was monitored as well as settings and filter adjusted according to the environment. The swath opening angle was set to 65° and the travieling speed was about 10 - 13 kn. As the data was collected during transit, no specific survey was performed. A sound velocity profile acquired during a previous cruise was applied in the MBES acquisition software SIS. The SVP data is not part of this submission. The data was post-processed using the software QPS Qimera. No further SVP re-computation, navigation correction or tide correction was applied. Erroneous depth measurements were deleted manually by using the swath and slice editor. The vertical datum is mean sea level (MSL). The cleaned data was exported in gsf format as well as bathymetric grids in a resolution of 100 m (geotiff format, geographic coordinates in WGS84 UTM zone 22N (EPSG: 32622) to 26N (EPSG: 32626). The coordinate system is indicated in the file name.